Transverse Load and Temperature Sensing Using Multiplexed Long-Period Fiber Gratings - Torres Gómez, Ismael; Martínez Ríos, Alejandro; Anzueto Sánchez, Gilberto; Ceballos Herrera, Daniel E.; Salceda Delgado, Guillermo (Molecular Diversity Preservation International, 2020)
The simultaneous measurement of transverse load and temperature using two long-period fiber gratings multiplexed in the wavelength domain is presented experimentally. For this, a mechanically induced long-period fiber grating (MI-LPFG) and a long-period fiber grating inscribed by a continuous-wave CO2 laser (CO2 LPFG) are connected in cascade. First, the transverse load and the temperature measurements were individually performed by the multiplexed long-period fiber gratings configuration. The MI-LPFG is subject to a transverse load variation from 0–2000 g with steps of 500 g, whereas the CO2 LPFG is unloaded and they are kept at room temperature. Similarly, the CO2 LPFG is subject to a temperature variation from 30 to 110 °C by increments of 20 °C, while the MI-LPFG with a constant transverse load of 2000 g is kept at room temperature. Subsequently, the simultaneous measurement of the transverse load and the temperature is performed by the multiplexed long-period fiber grating following the steps outlined above. According to the experimental results, the transverse load and temperature measurement present high repeatability for the individual and simultaneous process. Moreover, the multiplexed LPFGs exhibit low cladding-mode crosstalk of transverse load and temperature. The coarse wavelength-division multiplexing (CWDM) of long-period fiber gratings is an attractive alternative technique in optical fiber distributed sensing applications.